Using Gamma Ray Transmission for Determination of Porosity in Doped Alumina Samples - Al- Saadiand, A. J.; Saadon, A. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study, gamma ray transmission method have been used to determine the total porosity in four samples: pure Alumina ( Al2O3 ), Al2O3 + (0.2wt%)MgO , Al2O3 + (0.6wt% )Y2O3 and Al2O3+ (8wt% ) ZrO2 . The experimental setup for the gamma ray transmission consist of 137Cs gamma source ( 662 KeV ), a NaI (Tl) scintillation detector measured the attenuation of strongly collimated gamma beam through alumina samples. The porosity obtained by the gamma ray transmission method were compared with the measurements by conventional (Archimedes) method. It was observed that the porosity measurement by gamma ray transmission method has the advantage of being accurate, nondestructive and fast analysis.